2004
DOI: 10.1097/00124784-200407000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tobacco Control Policies on Smoking Rates

Abstract: This article reviews studies of the effect of tobacco control policies on smoking rates with the aim of providing guidance on the importance of different policies. Based on past studies, we estimate the magnitude of effects of major tobacco control policies, how their effects depend on the manner in which the policies are implemented, the relationship between the different policies, and the barriers to implementation. The most successful campaigns have implemented a combination of tobacco control policies. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
328
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 406 publications
(347 citation statements)
references
References 88 publications
10
328
3
6
Order By: Relevance
“…Evidence on the effectiveness of youth access policies is weak, with mixed effects across studies (Hopkins et al 2001;Levy et al 2004). Hopkins et al (2001) considered interventions with community mobilization and found a median decrease in smoking of 5.8 percentage points (translating to about a 20% relative decrease using a 30% last 30 day prevalence rate), with a range of 3.8 to 11 (or 13% to 37% in relative terms).…”
Section: Policy Modulesmentioning
confidence: 99%
“…Evidence on the effectiveness of youth access policies is weak, with mixed effects across studies (Hopkins et al 2001;Levy et al 2004). Hopkins et al (2001) considered interventions with community mobilization and found a median decrease in smoking of 5.8 percentage points (translating to about a 20% relative decrease using a 30% last 30 day prevalence rate), with a range of 3.8 to 11 (or 13% to 37% in relative terms).…”
Section: Policy Modulesmentioning
confidence: 99%
“…53 The proportion of families with income below the federal poverty level in 1999 was included to control for SES at the MSA-level of analysis. Finally, because higher state-level tobacco taxes may be associated with reduced smoking prevalence, [54][55][56] we included a measure of cigarette taxes (tax in dollars per pack of 20 cigarettes imposed by the state exclusive of any local taxes) 35 to control for potential confounding by variation in state-level tobacco control policies. The MSA population and the cigarette tax variable were log-transformed to correct skewness.…”
Section: Control Variablesmentioning
confidence: 99%
“…Many factors can affect quit attempts [5], including substantial increases in price and taxation [13], but as noted in the Introduction the last substantial national increase in cigarette prices was during the first half of 2009, limiting changes in price as a simple explanation for the phenomenon. The CDC Tips from Former Smokers (TIPS) campaign started in the first half of 2012, and pre-post analyses of population cohorts has demonstrated that TIPS increases quit efforts [14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Total smoking cessation in a population is the product of the proportion of smokers making a quit attempt multiplied by their success rate [4,5]. As a result, public health programs have focused both on boosting quit attempts and improving their success rate.…”
Section: Introductionmentioning
confidence: 99%